2010
DOI: 10.1007/s11676-010-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Rate of timber production in a tropical rainforest ecosystem of Southwestern Nigeria and its implications on sustainable forest management

Abstract: Timber harvesting data are very essential for sustainable management of forest resources. These data are very scarce in developing countries. Therefore, we collected and analyzed data on the rate of timber production of the free areas and the forest reserves in Ondo State, Nigeria. The data collected from the State Department of Forestry's official records, annual reports and files were on the species, volume and number of different economic timbers exploited on monthly basis between 2003 and 2005. Analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…As a result, there is reduction in tree species richness, abundance and evenness of the ecosystem (Lafrankie et al 2006) which is not creditable to biodiversity conservation. The tree species distribution into families agrees with the work of Adekunle et al (2010) who indicated that the tropical rainforest ecosystem of southwest Nigeria is dominated by some specific families such as the Sterculiaceae, Meliaceae, Moraceae and Ebeneceae. Isichei (1995) also reported that Nigerian rainforest ecosystem is dominated by members of Sterculiaceae, Moraceae, Ulmaceae and Meliaceae families.…”
Section: Discussionsupporting
confidence: 88%
“…As a result, there is reduction in tree species richness, abundance and evenness of the ecosystem (Lafrankie et al 2006) which is not creditable to biodiversity conservation. The tree species distribution into families agrees with the work of Adekunle et al (2010) who indicated that the tropical rainforest ecosystem of southwest Nigeria is dominated by some specific families such as the Sterculiaceae, Meliaceae, Moraceae and Ebeneceae. Isichei (1995) also reported that Nigerian rainforest ecosystem is dominated by members of Sterculiaceae, Moraceae, Ulmaceae and Meliaceae families.…”
Section: Discussionsupporting
confidence: 88%
“…The high number of species composition of Fabaceae and Moraceae in Nigeria rainforest has widely been documented (Salami and Lawal, 2018). This aligns with the findings of Adekunle et al (2010) and Adekunle (2016) who reported that families such as Sterculiaceae, Meliaceae, Moraceae and Ebenaceae dominate the tropical rainforest of southwest Nigeria. The ability of Moraceae to produce a large number of seeds and quickly establish itself may account for their high presence and this was confirmed by Deka et al (2012).…”
Section: Relative Importance Values Of Herbaceous Species In Wet and Dry Seasons Of Crin Secondary Forest Ibadan Nigeriasupporting
confidence: 91%
“…is a shade-intolerant, animaldispersed Boraginaceae species [27,30], considered to be of Least Concern on the IUCN Red List [31]. All three tree species are under pressure from logging in Nigeria [32][33][34]. These three species share a similar geographic range (from West to East Africa), though the distribution of African walnut is not as extensive as that of West African Cordia or tiama mahogany [28,29,31].…”
Section: Introductionmentioning
confidence: 99%